Persaudaraan Orang Muda Katolik: Perbandingan Dokumen Abu Dhabi dan Sinode Keuskupan Bandung 2015 - Leonardus Dewantara, Moses; Viktorahadi, R.F. Bhanu (Parahyangan Catholic University, 2023)
This research explores the role of Catholic Youth (Orang Muda Katolik or OMK) in responding to the challenges of intolerance in Indonesia, particularly in the province of West Java. By examining Catholic Church documents such as the